Aluminum-copper-boron nitride composite material and heat dissipation element comprising same

By adding BN particles to the Al-Cu alloy to form an aluminum-copper-boron nitride composite material, the problems of insufficient mechanical strength and thermal conductivity of existing heat dissipation elements in high temperature environments are solved, and the effect of efficient heat dissipation and improving the reliability of electronic components is achieved.

CN120164858APending Publication Date: 2025-06-17IND TECH RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311745788.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

The shell material of existing heat dissipation elements is insufficient in high temperature environments, resulting in a decrease in heat dissipation effect, and insufficient thermal conductivity cannot quickly reduce the surface temperature of the electronic component, affecting its reliability.

Method used

The aluminum-copper-boron nitride composite is used to add BN particles to the Al-Cu alloy and form the Al-Cu-BN composite material through mechanical alloy method and hot pressing molding method to improve its mechanical strength and thermal conductivity.

Benefits of technology

The aluminum-copper-boron nitride composite material has relatively high mechanical strength and thermal conductivity, which is suitable for the application of high-efficiency heat dissipation components and improves the reliability of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120164858A_ABST
    Figure CN120164858A_ABST
Patent Text Reader

Abstract

The aluminum-copper-boron nitride (Al-Cu-BN) composite material disclosed by the invention comprises Al-Cu alloy crystal grains, Al2Cu precipitates and BN particles, wherein the BN particles are positioned at the boundaries of the Al-Cu alloy crystal grains. The weight percentage of copper in the Al-Cu-BN composite material is larger than 0 wt% and smaller than or equal to 5 wt%, and the weight percentage of boron nitride in the Al-Cu-BN composite material is larger than 0 wt% and smaller than or equal to 1 wt%. The invention further provides a heat dissipation element comprising the Al-Cu-BN composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a composite material, and more particularly to an aluminum-copper-boron nitride composite material and a heat dissipation element containing the same. Background Art

[0002] The housing material of existing heat dissipation elements (such as cold plates) is mainly aluminum alloy; however, its mechanical strength and thermal conductivity are no longer sufficient for use in high-density, small-size, and high-power electronic components. Specifically, if the housing of the cold plate does not have appropriate mechanical strength, the appearance of the housing is likely to deform under high-temperature and severe environments, resulting in a decrease in its heat dissipation effect. Furthermore, if the electronic component cannot quickly reduce its surface temperature through heat conduction by the cold plate, the reliability of the electronic component will be reduced. Based on this, the research and development of materials with high mechanical strength and high thermal conductivity will affect the application and development of electronic components in the electronic field. Summary of the Invention

[0003] The present disclosure provides an aluminum-copper-boron nitride composite material with relatively high mechanical strength and thermal conductivity.

[0004] The aluminum-copper-boron nitride (Al-Cu-BN) composite material according to an embodiment of the present disclosure includes Al-Cu alloy grains, Al2Cu precipitates, and BN particles, where the BN particles are located at the boundaries of the Al-Cu alloy grains. The weight percentage of copper in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 5 wt%, and the weight percentage of boron nitride in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 1 wt%.

[0005] The present disclosure provides a heat dissipation element including this Al-Cu-BN composite material.

[0006] Based on the above, an embodiment of the present disclosure provides an aluminum-copper-boron nitride composite material, in which the Al-Cu alloy grains can endow the composite material with the effects of solid solution strengthening, fine grain strengthening, and precipitation strengthening of Al2Cu precipitates, and the boron nitride therein can endow the composite material with relatively high thermal conductivity. Based on this, when the aluminum-copper-boron nitride composite material according to an embodiment of the present disclosure is applied to a heat dissipation element, this heat dissipation element can have relatively high mechanical strength and thermal conductivity. Brief Description of the Drawings

[0007] Figure 1A X-ray diffraction patterns after qualitative analysis of the mixed powder after the ball milling process for 1 hour, 2 hours, 4 hours, and 8 hours respectively in Example 1.

[0008] Figure 1B For Figure 1AMagnified schematic diagram of the diffraction peak at 38 degrees therein.

[0009] Figure 2 It is a scanning electron microscope (SEM) image of the Al-Cu-BN composite material of Example 1.

[0010] Figure 3 It is a scanning electron microscope image of the Al-Cu-BN composite material of Example 2.

[0011] Figure 4 It is a scanning electron microscope image of the Al-Cu composite material of Comparative Example 1.

[0012] Figure 5 It is a scanning electron microscope image of the Al-Cu composite material of Comparative Example 2, which shows the Al-Cu composite material formed by a ball milling process for 8 hours.

[0013] Figure 6A It is a schematic diagram of a cold plate according to an embodiment of the present disclosure.

[0014] Figure 6B It is a photograph of the housing of the cold plate according to an embodiment of the present disclosure. Detailed Description of the Embodiments

[0015] The present disclosure can be understood by referring to the following detailed description and in conjunction with the accompanying drawings. It should be noted that, for the convenience of the reader's understanding and the simplicity of the drawings, only a part of the electronic device is shown in the multiple drawings of the present disclosure, and the specific elements in the drawings are not drawn according to the actual scale. In addition, the number and size of each element in the drawings are only for illustration and are not used to limit the scope of the present disclosure.

[0016] Some embodiments of the present disclosure provide an aluminum-based composite material. Specifically, it is an aluminum-copper-boron nitride (Al-Cu-BN) composite material. In this embodiment, the Al-Cu-BN composite material includes Al-Cu alloy grains, Al2Cu precipitates, and BN particles. Among them, the Al2Cu precipitates make the Al-Cu-BN composite material have relatively high mechanical strength, and the BN particles make the Al-Cu-BN composite material have relatively high thermal conductivity, which will be described in detail in the following experimental examples.

[0017] In some embodiments, the weight percentage of copper in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 5 wt%, and the weight percentage of boron nitride in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 1 wt%. When the boron nitride in the Al-Cu-BN composite material is greater than 1.5 wt%, it will be difficult to form the Al-Cu-BN composite material during the following hot pressing method, and the formed sheet is also prone to cracking. In one embodiment, the weight percentage of copper in the Al-Cu-BN composite material is greater than or equal to 3 wt% and less than or equal to 5 wt%, and the weight percentage of boron nitride in the Al-Cu-BN composite material is greater than or equal to 0.5 wt% and less than or equal to 1 wt%.

[0018] The disclosed Al-Cu-BN composite material is formed, for example, by mechanical alloying and hot pressing methods. The manufacturing process of the Al-Cu-BN composite material of an embodiment of the present disclosure will be introduced below, but the present disclosure is not limited thereto.

[0019] First, mechanical alloying is performed on the Al powder, Cu powder, and BN powder with the above-mentioned ratios. Mechanical alloying is, for example, a process that gradually achieves alloying by atomic diffusion. Specifically, the Al powder, Cu powder, and BN powder can be placed in a planetary ball mill, for example, to perform a ball milling process. During the ball milling process, the above-mentioned powders are subjected to the collision and extrusion of the grinding balls, causing severe plastic deformation, fracture, and / or cold welding of these powders. That is, these powders will be continuously refined, causing the atoms therein to diffuse, thereby obtaining alloyed Al-Cu-BN powder.

[0020] After that, hot pressing is performed on the alloyed Al-Cu-BN powder. In the embodiment of the present disclosure, the hot pressing method includes vacuum hot pressing sintering. Vacuum hot pressing sintering is, for example, a process that combines sintering and pressure forming. Specifically, the alloyed Al-Cu-BN powder can be placed in a patterned mold first, and then the mold containing the alloyed Al-Cu-BN powder is placed in a hot press furnace to simultaneously perform the pressing and sintering of the alloyed Al-Cu-BN powder. After vacuum hot pressing sintering of the alloyed Al-Cu-BN powder, heat treatment can be continued to precipitate Al2Cu particles (Al2Cu precipitates), thereby forming the Al-Cu-BN composite material.

[0021] In some embodiments, the Al2Cu precipitates have a particle size of 0.1 μm - 10 μm. For example, the Al2Cu precipitates may have an average particle size of about 5 μm, but the present disclosure is not limited thereto. Additionally, after vacuum hot pressing sintering and heat treatment of the alloyed Al-Cu-BN powder, BN particles are formed at the boundaries of the Al-Cu alloy grains, as shown, for example, in the following Figure 2 and Figure 3 In some embodiments, the BN particles have a particle size of 50 nm - 100 nm.

[0022] Based on this, in this embodiment, by performing mechanical alloying, Cu can be added to Al to form a solid solution, so as to achieve the effect of solid solution strengthening. Additionally, in this embodiment, mechanical alloying using a planetary ball mill can refine the Al-Cu alloy grains, such that the Al-Cu alloy grains have a particle size of about 45 μm - 210 μm, so as to achieve the effect of fine grain strengthening. Furthermore, in this embodiment, by performing a heat treatment process after the hot pressing forming method, Al2Cu precipitates with a particle size of 0.1 μm - 10 μm are precipitated, wherein the Al2Cu precipitates hinder the movement of the dislocations of the Al-Cu alloy grains and generate strain hardening, so as to achieve the effect of precipitation strengthening. Based on this, the Al-Cu-BN composite material of this embodiment can have relatively high mechanical strength.

[0023] Furthermore, after vacuum hot pressing sintering and heat treatment of the alloyed Al-Cu-BN powder of this embodiment, BN particles with a nano-scale particle size are formed at the boundaries of the Al-Cu alloy grains.

[0024] The Al-Cu-BN composite material of this embodiment has relatively high mechanical strength and thermal conductivity and is suitable for applications in heat dissipation elements, such as cold plates, but is not limited thereto.

[0025] Experimental Examples

[0026] The present disclosure will be described below through several experimental examples, but these experimental examples are only for illustrative purposes and are not intended to limit the scope of the present disclosure.

[0027] In this experimental example, the raw materials used to form the Al-Cu-BN composite material include: Al powder, Cu powder, and BN powder. Among them, the Al powder is purchased from J.T BAKER and has a purity of 99.9% and a particle size of 100 μm, the Cu powder is purchased from Alfa Aesar and has a purity of 99.5% and a particle size of 149 μm, and the BN powder is purchased from SIGMA-ALDRICH and has a purity of 99.8% and a particle size of 70 - 80 nm.

[0028] In this experimental example, mechanical alloying was carried out using a planetary ball mill; hot pressing was carried out using a graphite mold.

[0029] [Example 1]

[0030] First, the Al powder, Cu powder, and BN powder were proportioned to form a mixed powder including 3.0 wt% of Cu powder and 1.0 wt% of BN powder.

[0031] Next, the mixed powder was placed in a ball milling jar in a glove box filled with argon, and the ball milling jar containing the mixed powder was placed in a planetary ball mill for an 8-hour ball milling process to form an alloyed Al-Cu-BN powder. The parameters of the ball milling process were: the rotation speed was 350 rpm, and the forward and reverse rotations were alternately performed every 20 minutes.

[0032] Then, the alloyed Al-Cu-BN powder was hot-pressed at 600 °C under a pressure of 40 MPa for 2 hours while maintaining the temperature and pressure. Then, the temperature was raised to 400 °C and held for 3 hours for heat treatment and then cooled to obtain Specimen 1.

[0033] Figure 1A are the X-ray diffraction patterns after qualitative analysis of the mixed powder after 1 hour, 2 hours, 4 hours, and 8 hours of the ball milling process in Example 1, and Figure 1B is Figure 1A an enlarged schematic diagram of the diffraction peak at 38 degrees in

[0034] In Example 1, after 1 hour, 2 hours, 4 hours, and 8 hours of the ball milling process respectively, the mixed powder in the ball milling jar was qualitatively analyzed using an X-ray diffractometer (XRD).

[0035] From Figure 1A and Figure 1B it can be known that: (1) the alloyed powder includes Al, Cu, BN, and aluminum nitride (AlN); (2) as the time of the ball milling process increases, the diffraction peak of Al gradually shifts to the right, which means that the content of Cu diffused into Al increases with the increase of the time of the ball milling process; (3) the diffraction peaks of Cu and BN overlap, which means that there is still a small amount of Cu that has not reacted with Al, and most of the BN exists, that is, only a small part of the BN reacts with Al to form AlN.

[0036] Analyzing Specimen 1 with a scanning electron microscope (SEM), white precipitates can be seen. In addition, BN particles with a nanoscale particle size can be seen formed at the boundaries of the Al-Cu alloy grains, as shown in Figure 2as shown

[0037] Take specimen 1 for elemental analysis of the precipitate. It can be obtained from Table 1 and Table 2 below that the precipitate is an Al2Cu precipitate.

[0038] Table 1 shows the composition ratios of each element after elemental analysis of the Figure 2 white precipitate in, and Table 2 shows the composition ratios of each element after elemental analysis of the Figure 2 grains in. It can be seen from Table 1 and Table 2 that the white precipitate is an Al2Cu precipitate, and the grains are Al-Cu alloy grains.

[0039] [Table 1]

[0040] White precipitate Weight percentage (wt%) Atomic percentage (at%) Al 47.72 68.25 Cu 52.28 31.75

[0041] [Table 2]

[0042] Grain Weight percentage (wt%) Atomic percentage (at%) Al 98.90 99.53 Cu 1.10 0.47

[0043] [Example 2]

[0044] In Example 2, the steps for forming the Al-Cu-BN composite material are substantially the same as those in Example 1, and the main difference lies in: the ratio of Al powder, Cu powder, and BN powder is different. That is, in Example 2, the ratio of the mixed powder includes 3.0 wt% of Cu powder and 0.5 wt% of BN powder.

[0045] The mixed powder was subjected to planetary ball milling, hot pressing, and heat treatment in the same manner as in Example 1 to obtain specimen 2.

[0046] Perform the same structure and composition analysis on specimen 2 as on specimen 1. Referring to Table 1, it can be seen that there are precipitates of Al2Cu and BN particles with a nanoscale particle size formed at the boundaries of the Al-Cu alloy grains, as Figure 3 shown

[0047] Table 3 shows the composition ratios of each element after elemental analysis of the Figure 3 white precipitate in, and Table 4 shows the composition ratios of each element after elemental analysis of the Figure 3 grains in. It can be seen from Table 3 and Table 4 that the white precipitate is an Al2Cu precipitate, and the grains are Al-Cu alloy grains.

[0048] [Table 3]

[0049] White precipitate Weight percentage (wt%) Atomic percentage (at%) Al 48.89 69.26 Cu 51.11 30.74

[0050] [Table 4]

[0051] Grain Weight percentage (wt%) Atomic percentage (at%) Al 98.91 99.54 Cu 1.09 0.46

[0052] [Example 3]

[0053] In Example 3, the steps for forming the Al-Cu-BN composite material are substantially the same as those in Example 1, and the main difference lies in: the ratios of the Al powder, Cu powder, and BN powder are different. That is, in Example 3, the ratio of the mixed powder includes 5.0 wt% of Cu powder and 1.0 wt% of BN powder.

[0054] [Example 4]

[0055] In Example 4, the steps for forming the Al-Cu-BN composite material are substantially the same as those in Example 1, and the main difference lies in: the ratios of the Al powder, Cu powder, and BN powder are different. That is, in Example 4, the ratio of the mixed powder includes 5.0 wt% of Cu powder and 0.5 wt% of BN powder.

[0056] [Comparative Example 1]

[0057] In Comparative Example 1, the main difference in the steps for forming the Al-Cu-BN composite material compared to Example 1 is that: the raw materials do not include BN powder. In Comparative Example 1, the ratio of the mixed powder is 3.0 wt% of Cu powder and 97.0 wt% of Al powder.

[0058] The mixed powder was subjected to planetary ball milling, hot pressing, and heat treatment in the same manner as in Example 1 to obtain Comparative Specimen 1. As analyzed by a scanning electron microscope (SEM), white precipitates can be seen as Figure 4 shown.

[0059] Comparative Specimen 1 was taken for elemental analysis of the white precipitate, and it was found that the precipitate was Al2Cu. The elemental analysis is shown in Table 5, while the elemental analysis of the part of the Al-Cu alloy grains is shown in Table 6.

[0060] [Table 5]

[0061]

[0062]

[0063] [Table 6]

[0064] Grain Weight percentage (wt%) Atomic percentage (at%) Al 98.96 99.56 Cu 1.04 0.44

[0065] [Comparative Example 2]

[0066] In Comparative Example 2, the main difference from the steps of forming the Al-Cu-BN composite material in Example 1 is that: the raw materials do not include BN powder. In Comparative Example 2, the ratio of the mixed powder is 5.0 wt% Cu powder and 95.0 wt% Al powder.

[0067] The mixed powder was subjected to planetary ball milling, hot pressing and heat treatment in the same method as in Example 1 to obtain Comparative Specimen 2. It can be seen from the scanning electron microscope analysis that there are white precipitates as Figure 5 shown. Take Comparative Specimen 2 for elemental analysis of the white precipitate, and it is obtained that the precipitate is Al2Cu. The elemental analysis is shown in Table 7, while the elemental analysis of the Al-Cu alloy grain part is shown in Table 8.

[0068] [Table 7]

[0069] White precipitate Weight percentage (wt%) Atomic percentage (at%) Al 43.42 64.38 Cu 56.58 35.62

[0070] [Table 8]

[0071] Grain Weight percentage (wt%) Atomic percentage (at%) Al 97.94 99.11 Cu 2.06 0.89

[0072] [Comparative Example 3]

[0073] Comparative Example 3 provides an Al-BN composite material, the composition of which is 99.5 wt% Al and 0.5 wt% BN.

[0074] [Comparative Example 4]

[0075] Comparative Example 4 provides an Al-BN composite material, the composition of which is 99.0 wt% Al and 1.0 wt% BN.

[0076] [Comparative Example 5]

[0077] The material is 100 wt% Al.

[0078] The mechanical strength and thermal conductivity of Examples 1 to 4 and Comparative Examples 1 to 5 were tested below, and the experimental data are summarized in Table 9 below.

[0079] [Table 9]

[0080]

[0081] It can be seen from Table 9 that Examples 1 to 4 and Comparative Examples 1 to 2 have the following characteristics.

[0082] (1) The Al-Cu-BN composites of Example 1 and Example 2 and the Al-Cu composite of Comparative Example 1 both contain 3 wt% of Cu powder; however, the Al-Cu alloy material of Comparative Example 1 does not contain BN powder. Therefore, compared with the Al-Cu composite of Comparative Example 1, the Al-Cu-BN composites of Example 1 and Example 2 can have at least relatively high thermal conductivity.

[0083] (2) The Al-Cu-BN composites of Example 3 and Example 4 and the Al-Cu composite of Comparative Example 2 both contain 5 wt% of Cu powder; however, the Al-Cu composite of Comparative Example 2 does not contain BN powder. Therefore, compared with the Al-Cu composite of Comparative Example 2, the Al-Cu-BN composites of Example 3 and Example 4 can have at least relatively high thermal conductivity.

[0084] (3) The Al-Cu-BN composites of Example 2 and Example 4 and the Al-BN composite of Comparative Example 3 both contain 0.5 wt% of BN powder; however, the Al-BN composite of Comparative Example 3 does not contain Cu powder and cannot form Al2Cu precipitates. Therefore, compared with the Al-BN composite of Comparative Example 3, the Al-Cu-BN composites of Example 2 and Example 4 can have at least relatively high hardness and ultimate tensile strength.

[0085] (4) The Al-Cu-BN composites of Example 1 and Example 3 and the Al-BN composite of Comparative Example 4 both contain 1 wt% of BN powder; however, the Al-BN composite of Comparative Example 4 does not contain Cu powder. Therefore, compared with the Al-BN composite of Comparative Example 4, the Al-Cu-BN composites of Example 1 and Example 3 can have at least relatively high hardness and ultimate tensile strength.

[0086] (5) The material composition of Comparative Example 5 is only 100 wt% of Al, which has the worst thermal conductivity, hardness, and ultimate tensile strength among them.

[0087] [Heat Dissipation Use of Al-Cu-BN Composite Material]

[0088] The following is the use of the Al-Cu-BN composite material of the present disclosure in an embodiment, but the present disclosure is not limited thereto.

[0089] Figure 6A is a schematic diagram of a cold plate according to an embodiment of the present disclosure, and Figure 6B is a photograph of the housing of the cold plate according to an embodiment of the present disclosure.

[0090] Please refer to Figure 6A and Figure 6B, which shows a cold plate 10. The cold plate 10 can be, for example, a liquid-cooled plate and can be applied to electronic devices such as electric vehicles, etc., but the present disclosure is not limited thereto. In this embodiment, the material of the cold plate 10 is the above-mentioned Al-Cu-BN composite material. Based on this, the cold plate 10 can have relatively high mechanical strength and thermal conductivity.

[0091] In some embodiments, the cold plate 10 may include a housing 100 and a cover plate 200, but the present disclosure is not limited thereto.

[0092] The housing 100 is in contact with, for example, electronic components (not shown) in the electronic device to cool the electronic components by means of a working fluid flowing on the housing 100. Specifically, in this embodiment, the housing 100 has a flow channel 100P, where the working fluid enters through the inlet 100PI of the flow channel 100P and flows in the flow channel 100P, and the working fluid flowing in the flow channel 100P absorbs the heat generated by the electronic components in contact with the housing 100 and raises its temperature so that the electronic components can be cooled. After that, the working fluid with an increased temperature flows out of the housing 100 through the outlet 100PO of the flow channel 100P. In this embodiment, the working fluid is a liquid.

[0093] The cover plate 200 of the cold plate 10 is disposed on and connected to the housing 100, for example. In some embodiments, the cover plate 200 faces the flow channel 100P of the housing 100.

[0094] It is worth noting that although this embodiment exemplifies the application of the Al-Cu-BN composite material to the cold plate 10, the Al-Cu-BN composite material of the present disclosure can be applied to other heat dissipation components.

[0095] In summary, the Al-Cu-BN composite material of the present disclosure includes Al-Cu alloy grains, Al2Cu precipitates, and BN particles. The Al-Cu alloy grains are formed by adding Cu to Al to form a solid solution and performing mechanical alloying, which can have the effects of solid solution strengthening and fine grain strengthening. Furthermore, the Al2Cu precipitates hinder the movement of the dislocations of the Al-Cu alloy grains and generate strain hardening, which can have the effect of precipitation strengthening. The BN particles are formed by vacuum hot pressing sintering and heat treatment of alloyed Al-Cu-BN powder, and they are located at the boundaries of the Al-Cu alloy grains, whereby the Al-Cu-BN composite material of the present disclosure can have relatively high thermal conductivity. Generally speaking, the Al-Cu-BN composite material of the present disclosure can have relatively high mechanical strength and thermal conductivity, and can be applied to heat dissipation components such as cold plates.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aluminum - copper - boron nitride (Al - Cu - BN) composite material, characterized in that, It includes Al-Cu alloy grains, Al2Cu precipitates, and BN particles. Among them, the BN particles are located at the boundaries of the Al-Cu alloy grains. Among them, the weight percentage of copper in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 5 wt%, and the weight percentage of boron nitride in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 1 wt%.

2. The Al - Cu - BN composite material according to claim 1, wherein the Al2Cu precipitates have a particle size of 0.1 μm - 10 μm.

3. The Al - Cu - BN composite material according to claim 1, wherein the BN particles have a particle size of 50 nm - 100 nm.

4. The Al - Cu - BN composite material according to claim 1, wherein the Al - Cu alloy grains have a particle size of 45 μm - 210 μm.

5. The Al - Cu - BN composite material according to claim 1, wherein the weight percentage of copper in the Al - Cu - BN composite material is greater than or equal to 3 wt% and less than or equal to 5 wt%.

6. The Al - Cu - BN composite material according to claim 1, wherein the weight percentage of boron nitride in the Al - Cu - BN composite material is greater than or equal to 0.5 wt% and less than or equal to 1 wt%.

7. A heat dissipation element, characterized in that, It includes an Al-Cu-BN composite material, and the Al-Cu-BN composite material includes Al-Cu alloy grains, Al2Cu precipitates, and BN particles. Among them, the BN particles are located at the boundaries of the Al-Cu alloy grains. Among them, the weight percentage of copper in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 5 wt%, and the weight percentage of boron nitride in the Al-Cu-BN composite material is greater than 0 wt% and less than or equal to 1 wt%.

8. The heat dissipation element according to claim 7, wherein the heat dissipation element is a cold plate.